Development of creative cooperation skills of students (in the example of training future foreign language teachers) (Journal of Pedagogical Inventions and Practices, 2022)
The article examines the socio-pedagogical need for the development of creative cooperation skills in future Foreign Language teachers. Also, the structural structure of creative harmony, the possibilities of formation in the pedagogical process are highlighted.